Combined appendiceal goblet cell adenocarcinoma and low grade mucinous neoplasm: a case report with unusual presentation - Jain, Tanu; Rao, Rashmi; Jain, Vaibhav (International Journal of Research in Medical Sciences, 2024)
Appendiceal tumours are uncommon. They mostly present with abdominal pain due to appendicitis or as an incidental finding in an appendicectomy specimen. After neuroendocrine tumours (NETs), mucinous neoplasms are the most common appendiceal tumours. Goblet cell adenocarcinoma (GCA) is rare and exclusive in appendix. This is a distinctive subset of amphicrine tumour composed of both goblet and endocrine cells. They are more aggressive as compared to the conventional appendiceal tumours. Presence of both the tumours in the same patient is a rare instance. These synchronous tumours pose challenges for diagnosis as well as management. Here, we present a case of an 80 years old female with combined GCA and low grade appendiceal mucinous neoplasm.